Caterpillars’ natural enemies and attack probability in an urbanization intensity gradient across a Neotropical streetscape - Pena, João Carlos [UNESP]; Aoki-Gonçalves, Felipe; Dáttilo, Wesley; Ribeiro, Milton Cezar [UNESP]; MacGregor-Fors, Ian (Elsevier, 2021)
Intensification of urbanization has been shown to be associated with taxonomic and functional modifications of biological communities, leading to changes in trophic interactions. These changes may reduce the delivery of ecosystem services provided by urban ecosystems. For instance, predation on herbivorous insects is an important ecological process operating in urban biological communities. Specifically, on one hand, herbivorous insects serve as food resources for many organisms, and on the other hand predation on herbivorous insects may reduce pest populations on urban vegetation. In this study, we assessed the relationship between urbanization intensity and bird and arthropod predation pressure on herbivorous insects across the streetscape of Xalapa (Mexico), a Neotropical city with half a million people immersed in a cloud forest context. We exposed dummy caterpillar models at 16 sites across the streetscape and two sites in a peri-urban cloud forest patch, comprising a wide range of urbanization intensities. We observed that in streets where the proportion of built cover was higher, dummy caterpillars’ attack probability was substantially lower. Moreover, we observed that caterpillars were most often attacked by arthropods (62.41%), followed by birds (21.53%), independent of built cover. Our study provides evidence that built cover surrounding streets may negatively influence the interactions between herbivorous insects and their natural enemies.
Keywords: Herbivorous insects; Neotropical city; Pest control; Predator–prey interactions; Urban landscapes